Friendship, admiration, or hatred? The image of the united provinces in the travel diaries of the Czech nobility (1650-1750) - Jiří Kubeš (Theatrum Historiae)
The article deals with the “quality” of the relationship of the Czech nobility to the Northern Netherlands and its inhabitants. It is based on a research of different ego-documents (mainly diaries and correspondence). The author comes to the conclusion that the nobility from the Czech lands were not looking for friendship in the United Provinces in the second half of the 17th and the first half of the 18th century, as there were not many people there they could make friendly contact with. The local elite were predominantly made up of rich merchants and traders from the town establishment. If they did make any friends on their short visits, they were mostly recruited from the international diplomatic cream of society that frequented The Hague during the Baroque period. Thus the aristocracy from the Czech lands admired some things in the Northern Netherlands and its people, and hated others. Admiration (and perhaps envy) was inspired by the enormous economic successes of the local traders and merchants, ports full of boats, stores full of luxurious goods, outstanding lawyers in Leiden, clean and tidy towns and houses, the landscape with its many canals, avenues of trees, and an abundance of gardens. Words of praise always tended to be directed at the aesthetic form of these things, rather than their creators and the lifestyle they led. The Dutch mostly suffered condemnation at the pens of the Czech nobles, and in their words we can sometimes even read hatred for a nation which, in the view of the Central European nobility, did not respect the higher social status of the aristocrats and made life so complicated for the Catholics.